A Structural Review on Disaster Management Models and Their Contributions - Alrehaili, Naif Rashed; Almutairi, Yousef Naif; Alghamdi, Hamdan Mahmal; Almuthaybiri, Musaad S (TDMRC, Universitas Syiah Kuala, 2022)
This qualitative study aimed to undertake a critical examination of the models by thematic analysis to determine their contribution to disaster management. A review and analysis of the literature were used. The models were studied to explore their contribution to disaster management and to identify any significant constraints or challenges which could limit the ability of the models to carry out appropriate disaster risk reduction actions. The study found that such models are indispensable because they simplify and improve disaster management. Additionally, they may support planners, managers, and practitioners in reaching proper decisions, making them valuable and necessary decision-making support tools. The study also found that the four key phases of disaster management mitigation, preparedness, response, and recovery constitute the basis of the majority of models. The study also showed that each model has an advantage that distinguishes it from the other models. The findings also confirmed the doubts raised about the limitations and concerns associated with the models. Concerns included future disasters unpredictability, the models prescriptive nature, and the impact on businesses. The findings also indicated that certain planners, managers, and practitioners had a limited understanding of the use of models in disaster management. As such, they appear to have overlooked the use of models while dealing with disasters. Hence, the study recommends that the models should be employed in all disaster management phases. The study also recommends that the findings are utilized as a basis for further research into the potential use of disaster management models.